Choosing an electoral system: issues and alternatives - Lijphart, Arend; Grofman, Bernard (New York, 1984)
After several decades of indifference to electoral reform, the electoral system has again become a controversial question in many countries. Electoral laws are no longer regarded as unalterable facts, and there has been a renewed scholarly attention to the study of electoral systems. The aim of this book is to bring together in one volume, and in nontechnical form, all of the basic issues and all of the key alternatives for electoral choice, presented by scholars with widely varying electoral system preferences. We believe that Choosing an Electoral System is unique in that respect. The volume is not slanted for or against any particular system. The authors explore the factors that should be taken into consideration when political entities-from supranational organizations to local governments-choose their electoral systems, and the various alternatives from which choices can be made.
Keywords: Representative Government and Representation